The roles of blending and of molecular weight distribution on craze initiation - Sánchez-Valencia, Andrea; Smerdova, Olga; Hutchings, Lian R.; De Focatiis, Davide S.A. (American Chemical Society, 2017)
Craze initiation stress was measured in three-point bending isochronal creep tests on a series of entangled bimodal blends of polystyrenes of narrow dispersity, on three polystyrenes of broad dispersity, and on four blends of polystyrenes of broad dispersity. Crazing stress was found to increase rapidly with small additions of the higher molar mass component, quickly reaching a plateau. A simple model based on the weighted addition of the crazing stress contributions of the individual weight fractions obtained from an established piecewise linear crazing law was able to predict the crazing stress accurately in the bimodal blends using a power law exponent of 2.59 (90% CI [1.75–17.34]). In broad dispersity systems, in particular where short unentangled chains dilute the polymer, it was found necessary to modify the model using dynamic tube dilution theory. Dilution leads to a change in the entanglement length and hence in the molar mass at which transitions to disentanglement and chain scission crazing occur. With the improved model, crazing stress could be predicted even for the broad dispersity polymers with wide and bimodal distributions. This represents an opportunity for the molecular design of polymers by blending to achieve improved resistance to craze initiation.